Risk factors for fetal growth restriction in preterm births: a retrospective case control study - Charishma, Chinthala S.; Agarwal, Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Fetal growth restriction (FGR) and preterm birth (PTB) are two adverse pregnancy outcomes. There are many maternal risk factors that predispose to preterm and FGR independently. Very few studies have identified risk factors for combinations of preterm and FGR. The aim of the study was to find out whether risk factors for preterm FGR are different from the preterm non FGR. Methods: It was a retrospective case control study in which a total of 204 subjects (102 cases and 102 controls) were analyzed. Singleton, live as well as still births that occurred between 28+0 and 36+6 weeks of gestation were included in this study. FGR was defined as birth weight less than the 10th percentile as per intergrowth 21 charts. Odds ratios for the occurrence of preterm FGR and preterm non-FGR newborns, and respective 95% confidence intervals were estimated for each exposure variable. Results: Logistic regression analysis identified four significant risk factors for preterm FGR; low socioeconomic status (OR=1.9), manual labour (OR=12.9), BMI<18.5 kg/m2 (OR=9.2), passive smoking (OR=2.48). After adjusting these factors in multivariate analysis, underweight (OR=8.37) and manual work (OR=9.99) were found to be independent risk factors for FGR among preterm births. Conclusions: Interventions to promote early attendance to ANC services, reducing poverty, educating to avoid smoking and manual labour may significantly decrease the burden of FGR and preterm birth.